Fusion of Multiple Fiducial Markers for Continuous Teleoperation of Robot Arms - Bauer, Johanna; Rohrmüller, Martin; Dwivedi, Anany; Beckerle, Philipp (Conference Proceedings, 2023)
Teleoperated robots can safely explore remote or unknown locations, render help in hazardous environments, or lighten the load for rural healthcare providers. Unfortunately, many existing frameworks are either expensive, non-portable, or require complex room preparation. Therefore, a simple, flexible, portable, and low-cost teleoperation system based on optical motion tracking with fiducial markers for robotic arm systems is presented. Interfaces to wear the optical markers on the operator’s body and an algorithm to increase robustness by switching between multiple markers have been developed.<br
Keywords: ArUco; fiducial markers; data-fusion; robotics; teleoperation